Experience in a curricular internship in primary care occupational therapy: focus on infant health needs - Ruas, Teresa Cristina Brito; Leite, Fernanda Castilho; Akerman, Marco; Gagliardo, Heloisa Ravanini (ABCS Health Sciences, 2015)
Introduction: Attention to infant health in Brazil faces real problems concerning the effective accomplishment of transforming actions related to its practices, capable of meeting individual and collective demands related to its promotion, protection and recovery. Experience report: This study deals with the experience acquired by 4th year students of the Occupational Therapy course in a Basic Health Unit in the Santo André city with the implantation and development of actions related to the primary attention to the infant health in a Mandatory Curricular Probation since 2010. This report focuses the activities — guided by the methodological principle — reflection-action-reflection, developed in the toy room and in the monitoring of infant development. Conclusion: This experience acquired from children in a situation of social and/or biological vulnerability has shown us the urgent necessity of approaching the university to the local health necessities, thus enabling a professional practice with actions capable of recognizing and providing resources to empower and monitor the infant own characteristics.